An Analysis of Global, Direct and Diffuse Solar Radiation. (August 2015) - Li, Danny H.W.; Lou, S.W.; Lam, Joseph C.
Abstract: The paper studies the horizontal global, direct-beam and sky-diffuse solar radiation data measured in Hong Kong from 2008 to 2012, reports some of the general findings, evaluates mathematical model for predicting direct-normal solar radiation and computes various climatic variables. The findings can help to establish a more reliable and comprehensive solar radiation database for further building energy designs and assessments.